1035325 Keyakinan dan Sikap Orang Tua yang Mempengaruhi Keberhasilan Program Imunisasi Measles Rubella (Mr) - Bina Aquari (STIKes Budi Mulia Sriwijaya, 2019)
ABSTRACT In Indonesia, the MR immunization program still causes pros and cons, especially regarding the halal of the vaccine. This is supported by the absence of a halal certificate from the Indonesian Ulema Council (MUI). Beliefs and attitudes influence the success of the MR immunization program. Health workers must be able to provide clear counseling to parents about the importance of MR immunization. Indonesia has guaranteed the safety of MR vaccines, MR vaccines have been used in 141 countries and to date, there have been no reports of adverse effects of MR vaccines which are dangerous for children aged 9 months to 15 years. Only Indonesian countries have problems like this. This study is an analytical survey with a cross sectional approach. The sample of this study were all mothers who had children aged 9 months to 15 years totaling 62 people. Sampling using accidental sampling technique. Statistical test used chi square. beliefs and attitudes have a significant relationship to the success of MR immunization. Beliefs of parents who do not question halal or not lawful MR vaccine will lead to positive attitude of parents to bring and give their children MR vaccine. This statement is in line with Pratiwi's research which says that the factors that influence immunization in children such as knowledge, work, attitude. Keywords: Success of MR Immunizatio